Fluctuating ECG Change and Its Observation with Outcome in Acute Subarachnoid Hemorrhage - Sarker, Prosad Kumer; Md. Amjad Hossain Pramanik; Reza Nasim Ahmed; ABM Mahbubul Haque; Achinta Kumar Mallick; Muhatarima Tabassum; Md. Rokib Sadi (Bangladesh Journal of Neuroscience, 2026)
Background: Subarachnoid hemorrhage (SAH) is a serious neurological disorder that is often complicated by the occurrence of electrocardiographic abnormalities and may worsen the outcome. Therefore this study was designed to evaluate the role of fluctuating ECG patterns for predicting outcome in patients with SAH. Materials and Methods: This prospective observational study was conducted for 12 months at the department of Neurology in Rajshahi Medical College Hospital. A total of 40 patients with acute SAH were included. An informed written consent was obtained from the participants or from appropriate attendant. Detailed history was obtained from the participants including risk factor for developing SAH, concomitant morbidity. ECGs were routinely obtained at admission and then periodically as determined by the treating physician. Serial troponin levels and echocardiography were performed when ECGs are abnormal. Routine laboratory testing including complete blood count, serum potassium, blood glucose, serum creatinine etc. were performed in all the participants. Functional outcomes at hospital discharge were assessed with the modified Rankin Scale (mRS). Ethical clearance was obtained before beginning of the study from the ERC of the study place. Collected data was analyzed by using SPSS 22.0. Result: Mean age of the patients was 58.95±11.75 SD (years) with predominant female respondents (70%). Frequency of fluctuating ECG was 40% (n=16). Among the fluctuating ECG group 62.5% had e”2 changes in ECG followed by 12.5% had T wave inversion and 25% had ST segment change in fluctuating ECG group. Length of hospital stay was prolonged in fluctuating ECG group than normal ECG group (<0.05). Mean mRS at discharge was higher in fluctuating ECG patients than the normal ECG group (5±1.71 vs 2.83±2.07; 0.001) Overall poor outcome is associated with fluctuating ECG (p<0.05). Conclusion: The study showed that fluctuating ECG in SAH patients is closely linked with subsequent poor outcome of the patients.